Autophagy Flux Contributes to Regulation of Components of Eclipta prostrata L. on Cigarette Smoking-Induced Injury of Bronchial Epithelial Cells - Ding, Shumin; Hou, Xuefeng; Wang, Gang; Qiu, Huihui; Liu, Ying; Zhou, Yuanli; Du, Mei; Tan, Xiaobin; Song, Jie; Wei, Yingjie; Shu, Luan; Li, Zhiyong; et al. (Frontiers in Pharmacology, 2018)
Excessive autophagy plays a crucial role in cigarette smoking extract (CSE)-induced inflammation response and oxidative damage of respiratory epithelial cells. The components from Eclipta prostrata L. (CCE) have been shown to be benefical for CSE-induced epithelial cells injury. However, whether its protection on CSE-stress inury is related to its regulation on autophagy remains still unclear. In this study, CCE, containing mainly wedelolactone of 45.88% and demethylwedelolactone of 23.74%, could improve significantly 10%CSE-induced cell viability of normal human bronchial epithelial (NHBE) cells using CCK-8 kit. We revealed that CCE could remarkably increase autophagic factors Beclin-1, Atg5, ATF4 proteins expression levels and the transformation of LC3-I to LC3-II. Additionally, CCE up-regulated significantly p-p16 and p-p21 phosphorylation levels whereas down-regulated p-p53 in NHBE cells. The changes of typical autolysosom and representative autophgosome in the presence of CCE or/and autophagy inhibitor chloroquine (CQ) were also observed by transmission electron microscopy. These data demonstrated that CCE reduced CSE-induced autophagy flux activation in NHBE cells. The blockade of CCE on autophagy flux contributes to its protection aganist CSE-induced NHBE cells damage, and CCE is promising to be combination therapeutic molecules to excessive autophagic damage in respiratory diseases.